Harmonization between architectural components with natural forest environment through form, color, texture for Research and Education Forest in Malaysia - Jaafar, Nor Syuriaty; Hussein, Mohd Kher; Mohd Yusof, Mohd Johari (Penerbit Universiti Kebangsaan Malaysia, 2022)
The impact of the COVID19 pandemic has raised awareness regarding the vital role of forests as “environmental cleaners” that purifies our living environment. Public education in forest sustainability is a must whereby the Research and Education Forest would be the best medium to achieve this target. Although many researches have been conducted on forest conservation, studies on architectural design factors associated with the sensitivity of natural forest ecosystem remains enclosed. Hence, this study aims to investigate the significant correlation between the design elements of form, colour, texture and the harmonization of architectural components with natural environment in Research and Education Forest. The Pearson Correlation analysis revealed that all selected design elements correlated positively with the harmonious design factors on the architectural components. Meanwhile, the regression analysis also verified the proposed model statistically and the results proved that character of form, juxtapose of colour and feeling of texture are affecting the harmonization of architectural components. The findings conclusively determined that the design harmonization has a crucial impact on the architectural components in Malaysia’s Research and Education Forest.